1996
DOI: 10.1038/ng0696-147
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sex–specific quantitative trait loci controlling alcohol preference in C57BL/6 mice

Abstract: Mice from various inbred strains consume alcoholic beverages at highly reproducible and strain-specific levels. While most mice consume alcohol in moderate amounts, C57BL/6J animals exhibit sustained oral ingestion of high levels of alcohol in the presence of competing water and food. We now report a genetic investigation of this phenotype as one potential model for alcoholism. An intercross-backcross breeding protocol was used to identify two recessive alcohol preference quantitative trait loci (QTLs) that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
116
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(127 citation statements)
references
References 36 publications
10
116
1
Order By: Relevance
“…B6 mice consume large amounts of sweeteners (Lush 1989;Bachmanov et al 1996aBachmanov et al , 1996b, alcohol (Belknap et al 1993;Bachmanov et al 1996aBachmanov et al , 1996b and morphine (Forgie et al 1988) compared with the other mouse strains, and genetic correlations have been found between sweetener and alcohol intake in mice (Belknap et al 1993;Blizard and McClearn 1996;Bachmanov et al 1996a), suggesting that these behaviors may be affected by a common mechanism. However, quantitative trait loci modulating alcohol and morphine preference of B6 mice have been localized to Chrs 1, 2, 6, 10, and 11, but not to Chr 4 (Berettini et al 1994;Melo et al 1996). Although these results do not exclude the existence of loci with pleiotropic effects on these behaviors, they indicate that there are independent mechanisms influencing high consumption of sucrose, alcohol, and morphine by B6 mice.…”
Section: Discussionmentioning
confidence: 48%
“…B6 mice consume large amounts of sweeteners (Lush 1989;Bachmanov et al 1996aBachmanov et al , 1996b, alcohol (Belknap et al 1993;Bachmanov et al 1996aBachmanov et al , 1996b and morphine (Forgie et al 1988) compared with the other mouse strains, and genetic correlations have been found between sweetener and alcohol intake in mice (Belknap et al 1993;Blizard and McClearn 1996;Bachmanov et al 1996a), suggesting that these behaviors may be affected by a common mechanism. However, quantitative trait loci modulating alcohol and morphine preference of B6 mice have been localized to Chrs 1, 2, 6, 10, and 11, but not to Chr 4 (Berettini et al 1994;Melo et al 1996). Although these results do not exclude the existence of loci with pleiotropic effects on these behaviors, they indicate that there are independent mechanisms influencing high consumption of sucrose, alcohol, and morphine by B6 mice.…”
Section: Discussionmentioning
confidence: 48%
“…The first report of a sex effect on a QTL was that from Lee Silver's laboratory in a study of alcohol preference (Melo et al, 1996), confirmed by a follow-up study (Peirce et al, 1998). There have been four other reports of gender specific QTL that are less well substantiated because they are based on the observation that the LOD score is significant in one sex but not in the other.…”
Section: Mode Of Actionmentioning
confidence: 94%
“…It is important to note that the allelic effects on behavior in both QTL analyses were in the same direction with respect to B6/I, suggesting that the candidate at the Chr 8 locus should impact both behaviors in the same direction although other segregating loci may dissociate these effects. The negative genetic correlation may be accounted for by the several other overlapping preference and withdrawal loci segregating in inbred mouse populations such as Alcp1 (Melo et al 1996) and Alcw4 (Crabbe et al 1994) and Alcp18 (Gill et al 1998) and Alcw3 (Bergeson et al 2003). Finding other molecular substrates of the relationships among preference and withdrawal will enable better evaluation of competing mechanistic hypotheses.…”
Section: Discussionmentioning
confidence: 99%